Emotive connotations of the “big city” concept in the language of the Argentines - Yu. A. Larikova (Ибероамериканские тетради)
In the focus of the present study is the emotive-modal content of the “big city” (Buenos Aires) concept within the cultural worldview of the Argentines. On the basis of texts of two contemporary poets, Jorge Luis Borges (1899-1986) and Oliverio Girondo (1891-1967), the emotive semantics of words belonging to the Argentinian variety of Spanish, specifically actualized in poetic speech acts is analyzed.